2021
DOI: 10.3389/fpsyg.2021.681137
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Predictors of Quality of Life in Paediatric Patients With Sickle Cell Disease

Abstract: Sickle cell disease (SCD) refers to a group of inherited blood disorders with considerable morbidity that causes severe pain, reduces life expectancy, and requires significant self-management. Acute painful episodes are the hallmark of SCD, but persistent daily pain is also highly prevalent in this population. Characterising the impact and experience of SCD-related morbidity (i.e., sleep disruption, frequent emergency department visits, cognitive dysfunction) on health-related quality of life (HRQOL) requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…This finding is consistent with previous literature that examined healthcare utilization and HRQOL among youth with SCD. 28 Hood et al 29 found that frequent ER visits were associated with decreased HRQOL among youth with SCD and noted that increased ER visits may reflect increased pain. Pain is considered the "hallmark symptom" of SCD and is also one of the main reasons for hospitalizations 10,30 and decreased HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous literature that examined healthcare utilization and HRQOL among youth with SCD. 28 Hood et al 29 found that frequent ER visits were associated with decreased HRQOL among youth with SCD and noted that increased ER visits may reflect increased pain. Pain is considered the "hallmark symptom" of SCD and is also one of the main reasons for hospitalizations 10,30 and decreased HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the connection between poverty and HRQOL, our findings were comparable to previous research. 20,21 Even markers for poverty, such as parenting education level 22 and low income, 23 have been associated with decreased HRQOL in pediatric SCD. Factors associated with the connection between poverty and child HRQOL outcomes may in part be rooted in the long-term consequences of living in poverty.…”
Section: Discussionmentioning
confidence: 99%
“…61 In several studies, SCD severity and complications were associated with worse HRQoL. 44,60,65 In the association between hospitalization for VOC and HRQoL, the severity of hospitalization has not been taken into account before. According to our subanalysis, severity of hospitalization could have affected total HRQoL, but only until 3 months after hospitalization.…”
Section: Discussionmentioning
confidence: 99%